Economic Feasibility Study Of The HIPAM Clean Water Network System, Genting Village, Merjosari Village, Lowokwaru District, Malang City - Fandianto, Erno; Montarcih, Lily; Yuliani, Emma (International Journal of Science, Technology & Management, 2023)
The need for clean water for the community is urgently needed, therefore the HIPPAM (Drinking Water Users Association) was formed which is a legal forum according to government regulations and regulations to manage the supply of clean water to the community. There were many obstacles that occurred during operation, one of which was the regional regulation of East Java Province which required HIPPAM to pay groundwater withdrawal tax which ultimately affected the increase in the price of clean water. One area that was realized from the existence of this regulation was Genting Village, Merjosari Subdistrict, Lowokwaru District, Malang City. Given these problems, the purpose of this study is to analyze the economic feasibility of determining the price of clean water in the area. The results of this study show economic feasibility based on bank interest of 9%, Benefit Cost Ratio = 2.44, Net Present Value = Rp. 16,069,451,606, Internal Rate of Return = 13.99%, payback period = 13 years, and sensitivity analysis with IDR prices. 1,000/m3 and a 25% increase every 4 years following inflation.